Hubungan Indeks Massa Tubuh dan HDL dengan Laju Filtrasi Glomerulus pada Pasien Hipertensi di Klinik Media Farma Samarinda - Pahlevi, Muhammad Reza; Zubaidah, Mona; Rajibsman, Rajibsman (Jurnal Kesehatan Andalas, 2025)
Chronic Kidney Disease (CKD) is an irreversible, catastrophic condition. CKD is most commonly caused by hypertension, it is important to explore risk factors in hypertensive patients associated with Glomerular Filtration Rate (GFR) as an indicator of kidney function. Objective: To determined the relationship between risk factors, namely Body Mass Index (BMI) and High Density Lipoprotein (HDL), and how these factors influence GFR in hypertensive patients. Methods: This analytical observational study, using a cross-sectional approach, used 100 medical records from hypertensive prolanis patients at Media Farma Clinic, Samarinda, from January to December 2021. Statistical analysis was conducted using the Spearman correlation test, with p < 0.05 considered a significant correlation. Results: There were 40 male and 60 female patients. Among them, 51 patients had controlled blood pressure, while 49 had uncontrolled blood pressure. The median systolic blood pressure was 136.5 mmHg, and the mean diastolic blood pressure was 82.83 mmHg. The median age of the patients was 54.50 years. The median BMI was 27.23 kg/m², the median HDL was 41.5 mg/dL, and the median GFR was 73 ml/min/1.73 m². The relationship between BMI and GFR in hypertensive patients showed p = 0.034; r = 0.212. The relationship between HDL and GFR in hypertensive patients showed p = 0.020; r = 0.232. Conclusion: Both BMI and HDL have a significant positive correlation with GFR in hypertensive patients.  Keywords:  BMI, HDL, hypertension, GFR